Estimating the Knowledge-Capital Model of the Multinational Enterprise: Comment - Blonigen, Bruce A; Davies, Ronald B; Head, Keith (American Economic Review, 2003)
Estimating the Knowledge-Capital Model of the Multinational Enterprise: Comment by Bruce A. Blonigen, Ronald B. Davies and Keith Head. Published in volume 93, issue 3, pages 980-994 of American Economic Review, June 2003